Do conceito de controle da administração pública no Direito Administrativo brasileiro - Saad, Amauri Feres (2016)
This work aims at the conceptual definition of the public administration control activity in Brazilian law. Opposed to traditional formulations that confuse the control activity with other administrative activities, especially those related to the hierarchy, to the tutelage and "self-tutelage", this thesis rejects, in the concept of control of public administration, any formulations involving integration of the will on the part of the controlling entity towards the controlled entity. It defines control as verification of legality of state action. Established this basic concept, and demonstrated its difference in relation to the aforementioned activities, it passes on to the institutional control configuration in Brazil and summarization of legal criteria for control of government valid under the 1988 Constitution